33 best of / Tania Maria Tangit … [et al.] - Tangit, Tania Maria; Adanan, Akmal; Md. Hasim, Ahmad Khairuman; Shafie, Shamsol (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
"Melaka 33" is a useful pictorial guidebook, targeted to domestic and international visitors to the Historical State of Melaka. It summarizes the "33 Best of" unique tourism attractions, which comprises the cultures of its people, local cuisines and delicacies, must-visit places, and to-do itineraries. This guidebook will pioneer a comprehensive "Malaysia 33" after publishing "33 Best of" 13 Malaysian States and 3 Federal Territories. The uniqueness of this publication is within the "Features" section. Bold opinion leaders from various walks of life will be interviewed to share their "Top 3" favourite items of the Malaysian States. In a nutshell, this product would be the peoples' pride and joy to be a part of an exclusive publication, which highlights their culture and where they come from. At an economic standpoint, this publication allows various tourism related stakeholders to contribute to the worthiness of the publication for it to be used as a selling-point for all the Malaysian States. This easy-to-hold guide can be presented as gifts to international guests and delegates to Malaysia. The commercialization potential for "Melaka 33" and its subsequent series will place Melaka at the forefront and Malaysia in the eyes of the world. The publication may also be made free-of charge if and when tourism bureaus agree for the funding of the publication.